Dendritic Cells and Immunomodulation: Role in Health and Disease - Thokchom, Suresh K.; Gulati, Kavita; Thakur, Tarun; Rai, Nishant; Ray, Arunabha (Current Immunology Reviews (Discontinued), 2017)
Background: In this article, we aimed to discuss the current status of Dendritic cells (DCs), their subtypes, characteristics and role in immune responses and highlighted their therapeutic potential in selected diseases. Methods: A systematic and constructive analysis of peer reviewed research literature was done with reference to DCs and their functions, DC subsets and their general characteristics, role of helper T cells in health and diseases. We also conducted a narrative review of the relevant publications on DCs migration to secondary lymphoid organs and presentation of antigens to T lymphocytes in order to initiate antigen-specific immune responses. Further, emerging pharmacological targets of DCs have been discussed and they are suggested as leading targets for therapeutic immunomodulation in several chronic diseases. Results: A great body of evidence on the role of DCs in the induction of primary immune responses, promotion of immunological tolerance and in regulation of the activity of different types of effectors and regulatory T-cells involved in adaptive immune response has been discussed. The review has identified DC-based immunotherapy as a promising therapy for several diseases such as Job’s syndrome, respiratory diseases (allergy, asthma and COPD), tumor immunity, autoimmune disease, infectious diseases (tuberculoid and lepromatous leprosy, HIV infection), transplantations, metabolic disorders (type 1 diabetes) etc. Conclusions: The emergence of new classes of T-helper effector cells and their cytokines has led to a change in our understanding of therapeutic potentials of DCs. This has provided both new options and challenges for researchers involved in this field, and is likely to result in advancement in identifying and developing novel therapeutic measures and innovative strategies for several immunological chronic disorders.
Keywords: immunotherapy